2004
DOI: 10.1038/nbt1007
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to cure established tumors by inflammatory killing of normal cells

Abstract: We describe a simple technology used to cure an established metastatic disease. Intradermal injection of plasmid DNA encoding a transcriptionally targeted cytotoxic gene, along with hsp70, not only promoted tissue-specific, inflammatory killing of normal melanocytes, but also induced a CD8(+) T-cell-dependent, antigen-specific response in mice that eradicated systemically established B16 tumors. This CD8(+) T cell response was subsequently suppressed in vivo within a few days. The data demonstrate that deliber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 37 publications
7
131
1
Order By: Relevance
“…41 Indeed, the deliberate establishment of an autoimmune response against normal melanocytes has been proposed as a potential approach for promoting antimelanoma immunity. 42,43 Therefore, therapies that provoke immune activation in addition to direct tumour-specific cytotoxicity represent rational approaches to the treatment of MMM.…”
Section: Discussionmentioning
confidence: 99%
“…41 Indeed, the deliberate establishment of an autoimmune response against normal melanocytes has been proposed as a potential approach for promoting antimelanoma immunity. 42,43 Therefore, therapies that provoke immune activation in addition to direct tumour-specific cytotoxicity represent rational approaches to the treatment of MMM.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was not effective in therapeutic models, some studies that develop rapid antitumor responses have shown to be effective against established B16 tumors. 34 The use of future vaccine strategies against MUC18 may lead to a more rapid induction of immune responses with the ability to overcome established tumors. There may be a potential for autoimmunity when vaccinating against murine MUC18 in mice.…”
Section: Discussionmentioning
confidence: 99%
“…23 Herein, we demonstrate that this antibody can also be employed as a vaccine adjuvant with a preferential effect on linked class I/II peptide vaccines to engender antitumor efficacy against poorly immunogenic intracranial tumor. However, it is worth noting that while αhCD27 dramatically elevated vaccine immunogenicity, that there was variability in these responses despite age- and gender-matched genetically identical recipients.…”
Section: Discussionmentioning
confidence: 96%
“…C57BL/6 mice were obtained from Charles River Laboratories (Wilmington, NC, USA), and transgenic OT-I and OT-II mice were obtained from Jackson Laboratories (Bar Harbor, ME, USA). Human CD27 transgenic (hCD27) mice, which express both murine and human CD27 molecules under the native murine CD27 promoter, 23 were obtained from Celldex Therapeutics (Hampton, NJ, USA) and bred at DUMC. Homozygous hCD27 males were bred with C57BL/6, OT-I, or OT-II females to generate heterozygous hCD27, hCD27xOT-I, or hCD27xOT-II mice, respectively, for use in experiments.…”
Section: Methodsmentioning
confidence: 99%